2002
DOI: 10.1007/bf02505025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of classroom evaluation strategies on student achievement and attitudes

Abstract: This study investigated the effects of teacher evaluation and the combination of teacher evaluation and student self-evaluation on student performance and attitudes. Participants in the study were 189 Latvian high school students and their six teachers.The six teachers were assigned to one of three treatment conditions: (a) no evaluation, (b) teacher evaluation, and (c) self-evaluation plus teacher evaluation. All groups completed a 12-lesson instructional program on how to conduct experiments and produce re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
(30 reference statements)
0
26
0
Order By: Relevance
“…It is important to note that previous studies have found evidence that in challenging classes such as engineering classes, that there is no correlation between achievement and attitude/opinion 15,16,17 . Though this may be true, student opinion drives student action and therefore, results from the current study will allow professors to select which evidence-based practice/resource to devote time and resources to develop.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is important to note that previous studies have found evidence that in challenging classes such as engineering classes, that there is no correlation between achievement and attitude/opinion 15,16,17 . Though this may be true, student opinion drives student action and therefore, results from the current study will allow professors to select which evidence-based practice/resource to devote time and resources to develop.…”
Section: Discussionmentioning
confidence: 94%
“…Statistics tracking capabilities in Blackboard and YouTube, among others, will be investigated to confirm student reporting of use matches actual use. We will also include confidential identifiers in order to determine if the same students are surveyed multiple times for different classes.It is important to note that previous studies have found evidence that in challenging classes such as engineering classes, that there is no correlation between achievement and attitude/opinion 15,16,17 . Though this may be true, student opinion drives student action and therefore, results from the current study will allow professors to select which evidence-based practice/resource to devote time and resources to develop.…”
mentioning
confidence: 94%
“…Previous studies have found evidence that in challenging classes, achievement and attitude do not correlate [11][12][13] . Achievement was measured indirectly with final course grades.…”
Section: Discussionmentioning
confidence: 99%
“…Next to this, studies assessed the impact of the type of Effects of evaluation and assessment on student achievement assessments (such as e.g. oral tests, method-dependent assessments, method-independent assessments, diagnostic tests, tests as part of a student monitoring system (Bourke, 1986;Bosker et al, 1990;Carpenter et al, 2009;Meijnen, Lagerweij & De Jong, 1993;Olina & Sullivan, 2002). The average time (per week) teachers use for assessment Schaub & Baker, 1991) or the time teachers spent on scrutinizing of tests ) is a third category of operationalizations of assessment that are used in the studies included in the review.…”
Section: Assessmentmentioning
confidence: 99%